Social anxiety mediates workplace incivility and work engagement - Gan, Samuel Ken-En; Zeng, Yusong; Wang, Zihan (Frontiers in Psychology, 2023)
The average working person spends between 35-60 hours a week in the workplace, making it an influential place for mental well-being and a place for socioeconomic contribution. Workplace incivility can diminish positive mental health outcomes and negatively impact work engagement through increased social anxiety. To investigate this, 118 working adults in Singapore aged between 19 to 67 years old were recruited for a survey consisting of demographic questions, the Workplace Incivility Scale, Brief DSM-5 Social Anxiety Disorder Severity Scale, Utrecht Work Engagement Scale-9 between November 2022 to April 2023. Correlational, regression and mediation analysis showed workplace incivility scale scores to significantly predict social anxiety after controlling for covariates. This supports our hypothesis that employees exposed to workplace incivility would have higher social anxiety levels mediating work engagement after controlling for age and gender. The findings here show workplace incivility as a possible intervention target for social anxiety to reduce negative impacts on work engagement to improve employee experience and retention for organisations.